Pemodelan Pengenalan Penanda Augmented Reality Dengan Metaio Creator - Yudi Setiawan; Ridi Ferdiana; Rudy Hartanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
The research is about modeling marker recognition of Augmented Reality with Metaio Creator that desktop based, for getting information from a smartphone specification. This application is run by direct camera pc to marker, then application will give an augmented information about that smartphone. The augmented information are specification, and top features of smartphone. The testing is done by do the marker (natural printed AR marker) recognition process. The testers of that testing are a range of marker recognition and large of marker area that is recognized by AR application. The results are a good range of marker recognition, from marker to pc camera, and a good large of marker area. So user know a good range and area of marker to run Augmented Reality application.